SEROPREVALENCE OF TRANSFUSION-TRANSMITTED INFECTIONS AMONG VOLUNTARY BLOOD DONORS AT A TERTIARY CARE HOSPITAL - K, SHUNMUGAPRIYA; SA, MANIMALA; S, PUNITHARANJITHAM; RAVISHANKAR, JEYARAJ (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: Blood transfusion is an effective treatment for saving millions of lives. However, transfusion-transmitted infections (TTIs) hamper blood safety. To prevent transmission of these diseases, screening for infections is an essential step for blood safety. Aim: The aim of this study was to assess the seroprevalence of TTI among healthy voluntary blood donors. Methods: This was a retrospective cross-sectional study at the Department of Immunohematology and Blood Transfusion, Tirunelveli Medical College and Hospital, Tirunelveli, for a period of 6 years from January 2017 to December 2022. Data of the blood donors screened were retrieved and analyzed with the aid of screening register and seropositive donor register over 2 months (December 2022 and January 2023). Results: Among 53522 donors, 0.44% were seropositive for TTI (0.44%, n=233/53522) in which 99.57% (n=232/233) were male donors. Prevalence was more in 18–25 age group (39.91%, n=93/233). Hepatitis B virus (HBV) was the most prevalent microbe (n=144/53522) (0.27%). The prevalence of HBV showed a decreasing trend, while the prevalence of syphilis showed an increasing trend. The prevalence of human immunodeficiency virus, hepatitis C virus and malaria was unchanged. Conclusion: Seroprevalence and changing trends of TTI among blood donors reveal the prevalence of infections in the general population which gives an idea of disease burden on society. Education about confidential unit exclusion and implementation can help reduce transmission risk and wastage.